Ideological Archivism; Presenting a Conceptual Conformation of a Slanted Archival History - قربانی, یونس (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The following essay aspires to challenge a banal hypothesis in historical research; the phenomenon of inserting skewed historical data in documents and archives. This phenomenon is based on positivistic epistemology, and only in the traditional paradigm of historiography, in particular Ranke’s approach, is legitimate. Utilizing deconstructive criticism and contesting the positivistic perspectives, novel paradigms deem historical knowledge as an exploratory-inventive process, and put a special emphasis on its discursive structure. From this perspective, text generated in a particular social and cultural context construed as an ideological product. Accumulating this product in archives would not alter its nature to any extent. In particular, “the politics of archives” and “archiving instructions” convert this product into a raw material for ideological archivism. This essay is comprised of a set of theoretical argument as well as two case studies, giving a conceptual conformation of the construction of document-based history.